2006
DOI: 10.1093/jaoac/89.3.786
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Deltamethrin Residues in Plant Materials by Liquid Chromatography/Tandem Mass Spectrometry with Electrospray Ionization

Abstract: This paper describes a selective and sensitive method that uses liquid chromatography/tandem mass spectrometry with positive electrospray ionization (ESI+) for the determination of deltamethrin in a variety of crops. Samples were extracted by conventional high-speed blending. Some samples required no further cleanup; others were cleaned up by gel permeation chromatography, strong cation-exchange cartridges, or partitioning with n-hexane. In the determinative step, the buffered neutral mobile phase, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A possible contributing factor to the lack of sensitivity may be the form of the molecular ion, as pyrethroids were better detected with mass spectrometry as ammonium adducts . Although acidified ammonium formate was part of the mobile phase in this study, ammonium adduct formation was reported by others to improve when the mobile phase was buffered to pH 6.8 . Instrument and column performance may also change over time and affect sensitivity, suggesting that LOD and corresponding LOQ estimations should be measured at the time of each analysis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A possible contributing factor to the lack of sensitivity may be the form of the molecular ion, as pyrethroids were better detected with mass spectrometry as ammonium adducts . Although acidified ammonium formate was part of the mobile phase in this study, ammonium adduct formation was reported by others to improve when the mobile phase was buffered to pH 6.8 . Instrument and column performance may also change over time and affect sensitivity, suggesting that LOD and corresponding LOQ estimations should be measured at the time of each analysis.…”
Section: Discussionsupporting
confidence: 76%
“…43 Although acidified ammonium formate was part of the mobile phase in this study, ammonium adduct formation was reported by others to improve when the mobile phase was buffered to pH 6.8. 44 Instrument and column performance may also change over time and affect sensitivity, suggesting that LOD and corresponding LOQ estimations should be measured at the time of each analysis. Measuring the LOD during each run may allow harmonization across batches.…”
Section: ■ Discussionmentioning
confidence: 85%
“…5 Previous LC-ESI-MS studies of pyrethroids, including deltamethrin and permethrin, demonstrated that the primary ESI pathway was cation adduction. 26,27 In particular, ammonium adducts were reported to dominate the LC-MS spectra, and only a minimal amount of protonated species was observed. A number of TM-DESI solvents (e.g., methanol, acetonitrile, water-methanol solutions) were tested in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…43 Although acidified ammonium formate was part of the mobile phase in this study, ammonium adduct formation was reported by others to improve when the mobile phase was buffered to pH 6.8. 44 Instrument and column performance may also change over time and affect sensitivity, suggesting that LOD and corresponding LOQ estimations should be measured at the time of each analysis. Measuring the LOD and LOQ during each run may allow harmonization across batches.…”
Section: Discussionmentioning
confidence: 99%